Pengembangan Latihan Boomerang Run MenggunakanVideo Animasi Untuk Meningkatkan Teknik Dasar Dribbling Permainan Futsal SMPN 6 GARUT - Maulana, Muhamad Azis; Hermawan, Irwan; Hadi Kosasih, Alam; Arifin, Z. (Jurnal Speed (Sport, Physical Education, Empowerment), 2024)
Abstract In futsal, you are required to have and master basic techniques aimed at playing futsal skills. Players also need One of the dasar techniques is dribbling. Players of futsal must master the fundamentals of dribbling. need a training program so they can improve the basic techniques of Dribbling futsal for the better. This study used a type of experimental research with the One Group Pretest-Posttest Design, because this research aims to find out the development of Boomerang Run Exercises Using Video Animation to Improve Basic Dribbling Techniques for Futsal Games at SMPN 6 Garut. Twenty persons made up the overall population and twenty people made up the sample for this study, which used the futsal dribbling test instrument. Less than 30 people make up the study's relatively tiny population. Fourteen meetings were held to conduct the study. The findings of data processing using SPSS 22 were used to determine the average pretest and posttest values. Basic dribbling skills are significantly improved by the boomerang run training program that uses video animation, as seen by the average pre-test score of 2.65 and post-test score of 4.25. As a result, this training program is appropriate for enhancing the fundamental dribbling skills of SMPN 6 Garut futsal extracurricular students. Keyword: Dribbling, Futsal, Boomerang Run